CCR5 deficiency impairs CD4+ T‐cell memory responses and antigenic sensitivity through increased ceramide synthesis. (11th June 2020) - Martín‐Leal, Ana; Blanco, Raquel; Casas, Josefina; Sáez, María E; Rodríguez‐Bovolenta, Elena; de Rojas, Itziar; Drechsler, Carina; Real, Luis Miguel; Fabrias, Gemma; Ruíz, Agustín; Castro, Mario; Schamel, Wolfgang WA; et al.
Abstract: CCR5 is not only a coreceptor for HIV‐1 infection in CD4 + T cells, but also contributes to their functional fitness. Here, we show that by limiting transcription of specific ceramide synthases, CCR5 signaling reduces ceramide levels and thereby increases T‐cell antigen receptor (TCR) nanoclustering in antigen‐experienced mouse and human CD4 + T cells. This activity is CCR5‐specific and independent of CCR5 co‐stimulatory activity. CCR5‐deficient mice showed reduced production of high‐affinity class‐switched antibodies, but only after antigen rechallenge, which implies an impaired memory CD4 + T‐cell response. This study identifies a CCR5 function in the generation of CD4 + T‐cell memory responses and establishes an antigen‐independent mechanism that regulates TCR nanoclustering by altering specific lipid species. Synopsis: CCR5 deficiency and the ccr5 Δ32 polymorphism endow antigen‐experienced CD4 + T cells with a ceramide‐rich lipid environment, which restricts TCR nanoclustering. This reduces antigenic sensitivity and impairs CD4 + T:B cell cooperation for humoral responses after antigen re‐encounter. CCR5 provides antigen‐independent signals that regulate TCR nanoclustering in antigen‐experienced CD4 + T cells. CCR5‐induced TCR nanoclustering is independent of the CCR5 costimulatory activity on CD4 + T cells. CCR5 signals restrain transcription of ceramide synthase 2; this maintains control of the de novo Cer biosynthetic pathway and reduces ceramide levels. CCR5 maximizes restimulation of memory CD4 + T cells and production of high affinity class‐switched antibodies after antigen re‐encounter. Abstract : Modulation of the ceramide‐rich lipid environment by chemokine receptor and HIV‐1 co‐receptor CCR5 regulates nanoclustering of T‐cell receptors, to promote memory T‐cell responses and production of high‐affinity class‐switched antibodies.